2011
DOI: 10.1111/j.1743-6109.2011.02321.x
|View full text |Cite
|
Sign up to set email alerts
|

No (Wo)Man Is an Island—The Influence of Physicians' Personal Predisposition to Labia Minora Appearance on Their Clinical Decision Making: A Cross-Sectional Survey

Abstract: Introduction Physicians are increasingly presented with women requesting a labia minora reduction procedure. Aim To assess the influencing factor of personal predisposition in general practitioners, gynecologists, and plastic surgeons to labia minora appearance in relation to their willingness to refer for, or perform, a surgical labia minora reduction. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 21 publications
(42 reference statements)
0
21
0
1
Order By: Relevance
“…Media images, Internet advertising, physical discomfort, impedance of sexual activity, and dissatisfaction with appearance have been cited as indications. [5][6][7][8] Recently, research has evaluated female opinions of their own vulvar appearance as well as patient and physician definitions of normal anatomy to shed light on these issues. 4,9 In both US and European population surveys, most women were satisfied with their vulvar appearance; nevertheless, approximately 7% would consider labiaplasty.…”
mentioning
confidence: 99%
“…Media images, Internet advertising, physical discomfort, impedance of sexual activity, and dissatisfaction with appearance have been cited as indications. [5][6][7][8] Recently, research has evaluated female opinions of their own vulvar appearance as well as patient and physician definitions of normal anatomy to shed light on these issues. 4,9 In both US and European population surveys, most women were satisfied with their vulvar appearance; nevertheless, approximately 7% would consider labiaplasty.…”
mentioning
confidence: 99%
“…A study that has been cited in the media and was even discussed at the Australian Senate is a 2009 Dutch study that examined a physician's personal reactions to the labia minora appearance on their decision to refer or perform surgical reduction. The study found that plastic surgeons were more likely to find larger labia minora "distasteful and unnatural" compared to general practitioners and gynecologists [14]. Although the study does not directly apply to DSD, it has been used extensively to illustrate the biases that can influence clinical decision making, our difficulties to objectively define "normal" genital appearance and to argue against early genital reconstruction.…”
Section: Introductionmentioning
confidence: 98%
“…Plastic surgeons compared to general practitioners and gynecologists felt that large labia minora were distasteful and were more willing to operate given the same anatomy and patient concerns. Male practitioners were more inclined to opt for reduction than their female counterparts in the same specialties (Reitsma, Mourits, Koning, Pascal, & van der Lei, 2011). Women who are distressed with their genital appearance are likely to be unaware of the absence of standards for how labiaplasties are to done (Mirzabeigi et al, 2011).…”
mentioning
confidence: 98%